EDTECH PLATFORMS, E-LEARNING AND ENTREPRENEURSHIP IN INDIA: AN EMPIRICAL STUDY ON STUDENT ENGAGEMENT IN THE DIGITAL AGE (IITM Journal of Business Studies, 2025)
India’s EdTech industry has emerged as a global powerhouse, revolutionizing learning for over 400 million students, including 40 million in higher education, particularly during the COVID-19 pandemic. While EdTech platforms hold immense potential for digital learning and entrepreneurial skill development, their widespread adoption is hindered by challenges such as the digital divide, limited accessibility, and inadequate infrastructure. This study critically examines the influence of EdTech on student engagement, learning outcomes, and entrepreneurial aspirations within India’s digital education ecosystem.A mixed-methods research approach will be employed, integrating quantitative surveys and qualitative interviews. The study will survey 471 students from K–12 and higher education institutions across metropolitan and semi urban regions of India, alongside 25 EdTech entrepreneurs and 15 operational managers from leading EdTech firms. Data will be sourced from government reports, EdTech industry whitepapers, and academic literature. Descriptive statistics will be used to identify adoption trends to assess the impact of EdTech, while multiple linear regression will analyze the relationship between EdTech usage and student engagement. T-tests and ANOVA will compare engagement levels across demographic groups. PLS-Structural Equation Modelling (SEM) will explore the causal links between digital accessibility, AI-driven personalization, gamification, learning outcomes, entrepreneurial aspirations, and student engagement. Preliminary expectations suggest a strong correlation between EdTech usage and improved motivation, engagement, and academic performance. The study also anticipates higher retention rates than traditional e-learning methods and increased student interest in EdTech-driven entrepreneurship. It will conclude with strategic proposals aimed at filling digital accessibility gaps, improving personalization with AI, resolving parental issues of concern, and integrating entrepreneurial learning models so that the education provided is enhanced and the next generation of digital entrepreneurs is empowered.
Keywords: EdTech Platforms; Student Engagement; Entrepreneurial Aspirations; Online Learning Outcomes; Digital Entrepreneurship